2009
DOI: 10.1159/000190791
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity/Spirituality and Mortality

Abstract: Background: The relationship between religiosity/spirituality and physical health has been the subject of growing interest in epidemiological research. We systematically reviewed prospective observational cohort studies of the association between this potentially protective psychological factor and mortality using meta-analytic methods. Methods: We searched general bibliographic databases: Medline, PsycINFO, Web of Science and PubMed (up to 20 March, 2008). Two reviewers independently extracted data on study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(159 citation statements)
references
References 158 publications
7
145
2
5
Order By: Relevance
“…Thus, religious practices and acts of worship, especially at special times and in particular places, could lead to the regulation of the body's important physiological reactions (10). Experimental results have largely been compatible with the perspective that, through different mechanisms, religion is an important factor in preventing many diseases and the promotion of health (11,12). Gallup's opinion poll conducted in 1998 indicated that 60% of Americans reported religion to be of the utmost importance in their lives, and over 82% believed that they needed spiritual improvement, the survey thus confirming people's considerable concern with spirituality (13).…”
Section: Contextsupporting
confidence: 74%
“…Thus, religious practices and acts of worship, especially at special times and in particular places, could lead to the regulation of the body's important physiological reactions (10). Experimental results have largely been compatible with the perspective that, through different mechanisms, religion is an important factor in preventing many diseases and the promotion of health (11,12). Gallup's opinion poll conducted in 1998 indicated that 60% of Americans reported religion to be of the utmost importance in their lives, and over 82% believed that they needed spiritual improvement, the survey thus confirming people's considerable concern with spirituality (13).…”
Section: Contextsupporting
confidence: 74%
“…A considerable number of quantitative studies have so far found religious/spiritual variables to be modestly but meaningfully associated with mental or even physical health and psychosocial adjustment [2,4,5]. However, the research results are not entirely consistent; null findings and even negative associations were shown as well.…”
Section: Introductionmentioning
confidence: 93%
“…These results are in line with research with populations with other health conditions such as human immunodeficiency virus or Alzheimer disease or healthy populations. [120][121][122][123][124][125][126][127][128][129] Spirituality can be an important component in psychotherapy. [130][131][132] Beneficial effects of meaning making interventions on SE, optimism and self-esteem are reported.…”
Section: Psychological Resources In Sci C Peter Et Almentioning
confidence: 99%